Optimisation on pretreatment of kapok seed (Ceiba pentandra) oil via esterification reaction in an ultrasonic cavitation reactor - Chuah, L.F. (Springer Verlag, 2017)
Pretreatment of the kapok seed oil via esterification reaction has been investigated by using an ultrasonic cavitation reactor. Reaction parameters have been optimised by using response surface methodology and found as methanol to oil ratio of 16.23:1, catalyst amount of 9.94 wt and reaction time of 20.08 min at amplitude of 32.04 . The significance of the reaction parameters toward free fatty acid reduction was in the order of amplitude > reaction time > molar ration of methanol to oil > catalyst amount. The reaction time and esterified efficiency of ultrasonic cavitation was 4.5-fold shorter and 10.5-fold higher than mechanical stirring. The reactant used per produced biodiesel in ultrasonic cavitation process was about 2.6 lower compared to mechanical stirring process. © 2016, Springer-Verlag Berlin Heidelberg.